Sanitation predictors of childhood morbidities in Ethiopia: evidence from Dabat Health and Demographic Surveillance System - Zemichael Gizaw; Gashaw Andargie Biks; Mezgebu Yitayal; Geta Asrade Alemayehu; Kassahun Alemu; Tadesse Awoke; Adino Tesfahun Tsegaye; Amare Tariku; Terefe Derso; Solomon Mekonnen Abebe; Mulugeta Bayisa Chala (Komiyama Printing Co. Ltd, 2019)
Abstract Background Failure to provide adequate sanitation services to all people is perhaps the greatest development failure. Globally, billions of people have no access to improved sanitation facilities. Though the link between sanitation and childhood morbidities is established globally, the evidence is limited in rural parts of Ethiopia. This survey was, therefore, designed to determine the prevalence of common childhood morbidities and to identify sanitation predictors in rural parts of northwest Ethiopia. Methods A re-census reconciliation, which is a cross-sectional design, was employed from October to December 2014. All households found in the research and demographic sites were included as study subjects. A questionnaire and an observational checklist were used to collect data. Households' sanitation performances, house type, illumination, household energy sources, water supply, and waste management were assessed. The occurrence of childhood morbidities was determined from the occurrence of one or more water, sanitation, and hygiene (WASH) preventable diseases. Multivariable binary logistic regression analysis was done to identify the association of sanitation factors with childhood morbidities on the basis of adjusted odds ratio (AOR) with 95% confidence interval (CI) and p value < 0.05. Results About 575 (7.00%) of under-five children had hygiene- and sanitation-related diseases. Gastrointestinal and respiratory health problems accounted for 287 (49.91%) and 288 (50.09%), respectively. Childhood morbidities among under-five children were associated with poor housing condition [AOR = 1.27, 95% CI = (1.04, 1.54)], dirty cooking energy sources [AOR = 1.52, 95% CI = (1.22, 1.89)], volume of water below 20 l/p/d [AOR = 1.95, 95% CI = (1.19, 3.18)], and narrow-mouthed water storage containers [AOR = 0.73, 95% CI = (0.56, 0.96)]. Conclusion A significant proportion of under-five children had childhood morbidities in the study area. Housing condition, cooking energy sources, volume of water collected, and type of water storage containers were factors associated with the occurrence of childhood morbidities. Enabling the community to have the access to a safe and continuous supply of water and proper disposal of wastes, including excreta, is necessary with particular emphasis to the rural communities and semi-urban areas to reduce the occurrence of childhood morbidities.